Teacher Subject Knowledge, Didactic Skills, and Student Learning in Francophone Sub-Saharan Africa - Jan Bietenbeck; Natalie Irmert; Mohammad H. Sepahvand (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study the effects of two dimensions of teacher quality, subject knowledge and didactic skills, on student learning in francophone Sub-Saharan Africa. We use data from an international large-scale assessment in 14 countries that include individual-level information on student achievement and country-level measures of teacher subject knowledge and didactic skills in reading and math. Exploiting variation between subjects in a student fixed-effects model, we find that teacher subject knowledge has a large positive effect on student achievement, whereas the effect of didactic skills is comparatively small and not statistically significant at conventional levels. Together, the two dimensions of teacher quality account for 36 percent of the variation in average student achievement across countries.
Keywords: I21; I25; O15; 330; international learning gaps; teacher quality; Sub-Saharan Africa